Implementasi Math Club untuk Memperkaya Pengalaman Belajar Siswa SMP Negeri 2 Majene - Marlina Since Silong; Irmawati Irmawati; Ana Muliana; Sriwahyuni Sriwahyuni; Novianus Novianus (Penerbit Goodwood, 2026)
Purpose: This study aimed to apply a Math Club program to enhance students’ participation, confidence, and learning experiences in mathematics by creating an active, enjoyable, and meaningful learning environment. Research Methodology: The study was conducted at SMP Negeri 2 Majene over four months with nine students using a descriptive quantitative-qualitative design. Data were collected through observations, questionnaires, interviews, pre- and post-tests, and attendance records to evaluate changes in participation and mathematics-learning outcomes. Results: The results showed a significant improvement in students’ learning participation and engagement. The attendance increased from 60% to 85%. Active participation in asking questions and discussions increased from approximately 30% to 70%. Students’ mathematics test scores improved by 15–20%, and 75% of the students reported reduced anxiety and higher self-confidence. Conclusions: The Math Club program is an effective mathematics enrichment activity that enhances participation, achievement, and positive attitudes toward mathematics learning. Limitations: The study was limited by the small number of participants and implementation in only one school. Contributions: This study contributes to mathematics education by providing a practical enrichment model for teachers, schools, and teaching assistants to improve students’ engagement and learning experiences.